An Approach to Progress Monitoring of Industrial Manual Processes Based on Camera Recordings and Object Interactions - Mühlbauer, Matthias; Kutzner, Korbinian; Sommer, Alexander; Würschinger, Hubert; Hanenkamp, Nico (Procedia CIRP, 2022)
Despite digitalization and automation, manual processes in factory operations still play a significant role. With the increasing complexity of tasks, it is advisable to support the employee during execution. Technological progress regarding the analysis of image data facilitates the use of camera-based systems for assistance functions. A core element for these assistance systems is the recognition of state or actions to achieve context-sensitive support. However, existing solutions are often developed for specific problems and are difficult to transfer to other processes. This is especially the case for manual processes with more and different sub-process steps such as setup and maintenance operations. High development effort even in case of minor process changes is the result. Therefore, the objective of this work is to develop a generic approach for progress monitoring of manual processes. The proposed approach is based on the understanding that manual processes can be considered as the manipulation of objects to achieve a defined state of their characteristic properties. Consequently, manual processes can be described by their features, like the positions or movements of objects or their relative position to each other. To realize a configurable approach a two-step procedure is proposed. The basis is the flexible recognition and localization of objects in camera recordings by machine learning methods. Subsequently, the information obtained can be utilized by a configurable logic to verify defined states. To develop the detailed concept, firstly, a method for analysis of complex manual processes in factory operation is conducted. The aim is to determine and categorize the objects relevant for optical recognition and state verification. Secondly, different machine learning approaches for object recognition and object localization are compared to evaluate their capability in capturing the feature states. The possible outputs of the machine learning approaches are used to create control elements for progress verification. Examples are the position of objects in relation to each other or the speed of movement. In the next step, a procedure for the process-specific selection of the control elements is developed. Finally, the approach is applied and discussed. A setup process of a turning machine and a deburring process serve as representative use cases.
Created from Fastlane, Scopus look-up
Keywords: assistance system; machine learning; machine vision; Manual process; progress monitoring; state validation

Assessment of Process Improvement Potential of Carbon Dioxide as a Cryogenic for Machining Operations - Gross, Daniel; Hanenkamp, Nico; Heinz, Andrea; Ebner, Martin (Applied Mechanics and Materials, 2017)
Cryogenic machining offers advantages compared to conventional cooling lubrication strategies particularly for difficult-to-cut and high-temperature-resistant materials such as titanium and nickel alloys. For implementation purposes environmental and cost factors are crucial for this new machining approach in series production. In order to facilitate investments it is mandatory to evaluate the technology’s potential prior to the final implementation decision. In the field of machining, in particular machining with cryogenic process cooling, there is no standardized and uniform procedure to assess this potential. In this paper a systematic approach and underlying analysis tool will be introduced to determine the potential of cryogenic processing in terms of resources and energy efficiency of the manufacturing operation. This approach satisfies the general conditions in a reasonable assessment effort as well as in the detail level. With this analysis tool, real production and process data are compared with results from scientific cryogenic tests and research and examined with regards to their applicability. Thus, it is possible in an early stage of the production to identify potentials in manufacturing and to take measures to realize these effects. In case cryogenic processing of a specific material has not been carried out so far, the similarity of this material to existing research results is determined. If positively assessed, the surrogates’ potential is transferred with a specific safety factor to the material. The analysis tool has been applied and refined in a real large-scale series production as well as in a complex component manufacturing and the holistic potential for e. g. durability, material removal rate (MRR) or savings regarding the use of metal working fluids (MWF) have been identified.
Keywords: Carbon Dioxide; Cryogenic Machining; Large Scale Series Production; Potential Assessment

Audio Images: Analyzing impingement sounds of an air jet to develop a new tool wear measurement system - Würschinger, Hubert; Hanenkamp, Nico (Measurement, 2025)
Cutting tools are essential in machining processes, where knowing the condition of the tool is crucial to determining the optimal time for replacement. Various methods exist to assess tool condition, yet they are rarely applied due to challenges users face with these systems. This article provides background on a new approach for assessing and measuring tool wear using the impingement sound of an air jet. By scanning the surface with an air jet, an Audio Image is generated, enabling the reconstruction of surface details and the analysis of height variations, edges, and wear characteristics. Changes in the sound spectrum provide insights into surface variations, height differences, edge detection, and wear patterns. These findings open new possibilities for developing a Tool Condition Monitoring (TCM) system capable of reconstructing wear in three dimensions, offering more detailed and cost-effective analysis compared to existing methods.
CRIS-Team Scopus Importer:2025-02-17

Automated Data Labeling and Anomaly Detection Using Airborne Sound Analysis - Mühlbauer, Matthias; Würschinger, Hubert; Polzer, Dominik; Ju, Shu; Hanenkamp, Nico (Procedia CIRP, 2020)
Anomaly detection is facing the challenge of generating a maximum of information with a limited number of sensors in production machines and minimal effort of data analysis. Machine operators are often able to perceive changes acoustically and based on experience. In order to imitate this intelligent human capability, a systematic methodology has been developed in this work. Firstly, an introduction to this topic will be given and the acoustic sensor set up as well as the data preprocessing will be described. Secondly, an approach for automatic data labeling as an input for the intelligent anomaly detection will be presented. Using a model-based approach, anomaly detection is performed in the next step. This allows not only the detection of gradual and sudden process changes but also systematic problem solving. Finally, the anomaly detection will be validated for cutting processes.<br
Keywords: Anomaly Detection; Automated Data Labeling; Process Monitoring; Airborne Sound; Cyclic Production Processes; Cutting Processes

Bauteilfinishing durch CO2-Trockeneisstrahlen - Automatisierbare Nachbearbeitungsprozesse durch innovative Fertigungstechnologien - Amon, Sven; Gross, Daniel; Hanenkamp, Nico (wt Werkstattstechnik - Online, 2019)
Zur Produktivitätssteigerung ist eine ganzheitliche Optimierung von Prozessketten erforderlich. Auch innovative Fertigungstechnologien wie die additive Fertigung fordern ressourcenintensive und nicht-wertschöpfende Nachbearbeitungsprozesse. Das Entfernen von verfahrensbedingten Fertigungsrückständen sowie Materialanhaftun-gen wie Stützstrukturen ähnelt der Gratbeseitigung subtraktiver Fertigung. Für beide Herausforderungen bieten CO2-basierte Strahl-verfahren einen effizienten Lösungsansat
Keywords: Fertigungstechnik; Additive Fertigung; Automatisierung

CHARACTERIZATION OF METAL WORKING FLUIDS USING TRIBOLOGICAL TESTING METHODS - Ostrowicki, Nicolai; Markert, Johannes; Hanenkamp, Nico (MM Science Journal, 2021)
The objective of this paper is to determine whether it is possible to compare the lubricating properties of different Metal working fluids (MWF) for a defined cutting application using easily reproducible tribological tests. The idea is that this will eventually allow users of MWF to select the most suitable MWF for a specific application without the need to run expensive and time-consuming tests on a machine tool being unavailable for production during that time. The test method chosen is the Pin-on-Disc (PoD) test, as there has been extensive research and an easy setup can be acquired inexpensively, making it more available and attractive for potential users. The PoD-tests were done with two groups of MWF, those for wet machining and those for minimum quantity lubrication (MQL). Additionally, the viscosity of the MQL-MWF has been measured using a capillary viscometer. The evaluation of the wear on the pins and discs with different measuring devices shows consistent and promising results for the comparison of MQL-MWF, while the MWF for wet machining display only limited comparability with the PoD-setup used.
CRIS-Team WoS Importer:2021-11-26

Comparison of linear and trochoidal milling for wear and vibration reduced machining - Gross, Daniel; Friedl, Fabian; Meier, Trixi; Hanenkamp, Nico (Procedia CIRP, 2020)
Vibrations during milling lead to frequent tool replacements. This results in an unsteady load on the machine, which leads to increased tool wear, poor surface quality and therefore strong economic and ecological burden. Self-excited vibrations are influenced by the machining conditions, such as the workpiece geometry or the tool path generated by the used computer-aided manufacturing (CAM) software. This article compares linear and trochoidal milling in terms of vibration behavior and resulting wear phenomena by machining different component geometries. The results show, that trochoidal milling is not a suitable strategy to reduce vibrations and tool wear compared to linear milling.
CRIS-Team Scopus Importer:2020-10-23
Keywords: CAM; Milling; Milling strategy; Tool path optimazation; Vibration; Wear

Comparison of sprayability and solubility of bio-based lubricants with liquid carbon dioxide - Meier, Trixi; Gross, Daniel; Hanenkamp, Nico (MM Science Journal, 2021)
In recent years, cryogenic minimum quantity lubrication (CMQL) has been established in comparison to pure cryogenic cooling. The used oil has a crucial influence on the success of the technology. The aim of this study is to investigate the influence of oils from renewable resources with regard to their miscibility with carbon dioxide (CO2) and their spraying behavior. Ten different bio-based oils (synthetic ester, natural ester and fatty alcohol) have been examined regarding their suitability for CMQL compared to a conventional mineral hydrocrack oil. A validation based on sprayability and solubility properties with liquid CO2 has been performed. The sprayability and the resulting oil droplet size have an impact on the amount of oil entering the process zone and thus on the lubrication performance of the coolant concept. For this reason, a high-speed camera has been used to capture shadow images of the jet from an external cooling nozzle. In addition the width, intensity and uniformity of the oil application were evaluated. The solubility of the bio-based oils in CO2 is investigated in a static mixing chamber with varied mixing ratio. The miscibility of the bio-based oils in a single channel supply system was investigated with high-speed recordings of a dynamic mixing chamber. The results of the various experimental setups have been compared.<br
Keywords: CMQL; milling; turning; bio-based oils; carbon dioxide

Cutting force and vibration prediction of milling processes regarding the nonlinear behavior of cascade controlled feed drives - Ju, Shu; Gross, Daniel; Hanenkamp, Nico (Production Engineering, 2022)
Milling processes are characterized by their high degree of flexibility regarding shape creation and thus occur in many value adding processes in the electrical and mechanical engineering industry. To facilitate the systematic prediction and the efficient optimization of the process performance, a holistic simulation model of the milling process with cascade controlled feed drives is developed. The integrated model consists of two subsystems, namely the feed drive model and the process model. In the feed drive model, the dynamic models of the electric motors, the serially connected torsional oscillators of the mechanical elements and the cascade control system are established. In this model, the coordinate point of the milling tool is computed at each discrete time step and assigned to the process model. The cutting forces and the corresponding load torques are calculated in the process model and sent back to the feed drive model. In addition, practical validation of the complete system has been conducted both in the time and the frequency domain. The simulation results yield an accurate prediction of the tooth passing frequency with a variance of less than 1%. Moreover, the influence of the cascade control parameters and the nonlinear behavior of the electric motor on the process vibrations have been experimentally verified.<br
Keywords: Milling process simulation; Cascade control model; Cutting force prediction; Vibration prediction

Demonstration of a new approach for measuring tools with the impingement sound of an air jet using machine learning - Würschinger, Hubert; Gross, Daniel; Stadler, Manuel; Mühlbauer, Matthias; Hanenkamp, Nico (MM Science Journal, 2021)
Monitoring the tool condition of machining processes is important but challenging. Several automated tool condition monitoring solutions are available, but often not used due to existing restrictions or disadvantages. A new approach can be the detection and measurement of tool conditions analyzing the sound of an air jet impingement on tools. Due to the availability of compressed air as a working and cleaning medium for many processes, this approach can be used for various condition monitoring and measuring tasks. In this paper the procedure and its functionality are first presented on simple shapes and then tested on the tool wear of inserts.<br
Keywords: Tool Condition Monitoring; Condition Monitoring; Impingement Sound; Jet Impingement; Air Jet; Flow Noise; Airborne Sound; Machine Learning

Deviation Detection in Production Processes based on Video Data using Unsupervised Machine Learning Approaches - Mühlbauer, Matthias; Epp, Henrik; Würschinger, Hubert; Hanenkamp, Nico (Procedia CIRP, 2022)
The detection of deviations within production processes is essential to ensure high productivity or avoid potential damage. Various approaches are available for this purpose. In the field of video surveillance, unsupervised machine learning methods have made significant progress in detecting deviations. In this paper, the transferability of these generic approaches to production processes is investigated. At first, an evaluation basis is created. Therefore, the variety of deviations, which can occur in an automated production process, is structured and covered as far as possible in video benchmark data sets. Subsequently, existing unsupervised approaches are selected, adapted and tested on the created data sets. In conclusion, the results show that the two chosen unsupervised autoencoder architectures can be partially used for generic deviation detection in the production domain. The main challenges identified are the large variety of different tasks and deviations in production processes. However, for further investigations, the development of even more detailed benchmark sets is essential.
CRIS-Team Scopus Importer:2022-12-09
Keywords: anomaly detection; autoencoder; computer vision; deviation detection; Production process; unsupervised learning; video data

ECO2il - Entwicklung biobasierter Metallbearbeitungsöle für die kryogene Minimalmengenschmierung : Schlussbericht zum Vorhaben : Laufzeit: 01.06.2019 bis 31.05.2022 - Meier, Trixi; Hanenkamp, Nico (2023)
Ein Großteil der spanenden Metallbearbeitungsprozesse wird aktuell durch große Mengen flüssiger Kühlschmierstoffe unterstützt. Aufgabe des Kühlschmierstoffs ist es, die Kühlung und Schmierung des Werkzeugs im Eingriff sicherzustellen sowie die Späne aus dem Bearbeitungsraum abzutransportieren. Die Anwendung konventioneller insbesondere wassermischbarer Kühlschmierstoffe in Zerspanungsprozessen wirkt sich negativ auf ökonomische und ökologische Faktoren sowie auf die Gesundheit der Mitarbeiter am Arbeitsplatz aus. Aus fertigungstechnischer Sicht stoßen konventionelle Kühlschmierstrategien bei der Bearbeitung neuartiger Hochleistungswerkstoffe an ihre Leistungsgrenzen. Ein Ansatz konventionelle Kühlschmierstoffe im spanenden Bearbeitungsprozess zu ersetzen bietet sowohl die Minimalmengenschmierung als auch die kryogene Kühlung mittels CO2. In diesem Projekt soll die Entwicklung biobasierter Schmierstoffe für die kryogene Zerspanung kombiniert mit Minimalmengenschmierung durchgeführt werden. Im Fokus stehen dabei Prozesse mit geometrisch bestimmter Schneide. Ziel ist es, anwendungsnah Schmierstoffe biologischen Ursprungs für die kryogene Minimalmengenschmierung zu entwickeln, diese bedarfsgerecht zu additivieren und zu optimieren. Dadurch soll sichergestellt werden, dass sowohl die Werkzeugstandzeit als auch Zeitspanvolumina im Vergleich zu konventioneller Überflutungskühlung gesteigert werden können. Die dadurch erreichbaren ökologischen Verbesserungen stellen den Kern dieses Projektes dar. Industrielle Anwender sollen dahingehend unterstützt werden, dass Bearbeitungsprozesse mit aktuell konventioneller Überflutungskühlung auf Minimalmengenschmierung in Kombination mit kryogener CO2 Kühlung umgestellt werden können. Dadurch werden sowohl ökonomische und ökologische Vorteile erzielt als auch die Leistungsfähigkeit der Fertigungsprozesse erhöh

Effect of various cooling lubricant strategies on turning Inconel 718 with different cutting materials - Ostrowicki, Nicolai; Kaim, Alexander; Gross, Daniel; Hanenkamp, Nico (Procedia CIRP, 2021)
Due to its resistance to high temperatures and corrosion, Inconel 718 has a wide range of applications, particularly in the chemical and aerospace industry. The aim of this study is to investigate the potential of turning Inconel 718 with regard to tool life, depending on various cooling lubricant strategies and cutting materials. The reference process is flood cooling with carbide tools. Based on this, the process with carbide and CBN tools under dry machining, cryogenic cooling and cryogenic minimum quantity lubrication will further be investigated. Cutting forces, tool wear, roughness and chips are analyzed. Cutting length, surface quality and sustainability can be improved by using CBN and cryogenic minimum quantity lubrication (CMQL).<br
Keywords: Inconel 718; CBN; turning; cryogenic; cryogenic minimum quantity lubrication

Energieeffizienz durch Oberschwingungsreduzierung*/Energy efficiency through harmonic distortion reduction – Harmonics-minimized control strategy in production machines - Ju, Shu; Hanenkamp, Nico (wt Werkstattstechnik - Online, 2019)
Oberschwingungen ausgelöst durch frequenzgeregelte Antriebe wirken sich stark negativ auf den Energieverbrauch aus. Diese Oberschwingungen verstärken sich immer dann, wenn schnelle Drehzahländerung aus Produktivitätsgründen notwendig wird. Eine neue Steuerungsstrategie wird entwickelt. Durch Erhöhung des Grundschwingungsanteils im Motorsteuersignal lässt sich eine bis zu 20 % höhere Energieeffizienz erreichen. Ein Modell einer Bibliothek wird entwickelt. </
Keywords: Energieeffizienz; Steuerungstechnik

Energy Efficiency Assessment of Cryogenic Minimum Quantity Lubrication Cooling for Milling Operations - Gross, Daniel; Hanenkamp, Nico (Procedia CIRP, 2021)
Cryogenic minimum quantity lubrication (CMQL) extends the application spectrum of cryogenic cooling by the possibility of lubrication. This enables the proportion of both cooling and lubrication capacity to be adapted to the process as required. Especially liquid CO2 has been established for the CMQL. This application enables a sustainable use of CO2 in a circular cycle opposed to its emission to the atmosphere. For a comparison of conventional flood cooling with CMQL, the specific energy has to be determined in addition to the process-related suitability. Specifications by the European Commission and the desire for sustainable production require a quantification of the environmental impact. For the determination of these product carbon footprints, energy demand forecasts are essential. This paper presents a method for calculating the energy demand for milling processes under CMQL and wet machining according to the life cycle assessment EN ISO 14044 taking the material flows into account. The considered material flows include the cutting energy of the process, the energy to provide the water for the emulsion for flood cooling, the energy to liquefy the CO2, the energy for the oil refining process for emulsion and CMQL, the energy for the coolant pumps and the energy for the manufacturing of the tools. The balancing is carried out for a defined functional unit. Due to the different tool lifetimes, there are large fluctuations in the energy requirements. It is shown that despite the high energy expenditure for the provision of CO2 and the energy supply for flood cooling, the most significant influence on the energy expenditure results from the manufacture of the tools. By increasing the tool life and increasing the number of tool regrinding cycles, the energy requirement for the functional unit can be reduced.<br
Keywords: CMQL; flood cooling; energy efficiency; LCA; milling

Energy Efficiency in Production Machines Through Harmonic Distortion Reduction - Ju, Shu; Hanenkamp, Nico (IEEE PES Asia-Pacific Power and Energy Engineering Conference, 2019)
With the growing trend towards massive utilization of power electronics, the effect of harmonic distortions on not only power grids but only other system components is non-negligible. In this document, the source and effect of harmonic distortions are described. Latest state of harmonic distortion reduction technologies was researched and briefly depicted. Because of the technological limitations of the current methods, a control strategy by adjusting motor speed change trajectories in order to generate less harmonic distortions in motor acceleration and deceleration processes has been developed. The implementation needs only control software changes and no hardware installation. Based on sufficient simulation results, experiments have been carried out on a lab-constructed motor test bench. Optimized motor speed change trajectories with time-delayed transfer elements have been adjusted and put into operation, ensuring up to 20% energy saving potential during the motor speed changing phases. Energy efficiency can be achieved by applying the optimization method to any use case of power electronic actuators characterized by a highly dynamic machining proces
Keywords: Energy efficiency; harmonic distortion; machining; optimization methods; variable frequency drives

Energy Profile Prediction of Milling Processes Using Machine Learning Techniques - Mühlbauer, Matthias; Würschinger, Hubert; Polzer, Dominik; Hanenkamp, Nico (Machine Learning for Cyber Physical Systems, 2020)
The prediction of the power consumption increases the transparency and the understanding of a cutting process, this delivers various potentials. Beside the planning and optimization of manufacturing processes, there are application areas in different kinds of deviation detection and condition monitoring. Due to the complicated stochastic processes during the cutting processes, analytical approaches quickly reach their limits. Since the 1980s, approaches for predicting the time or energy consumption use empirical models. Nevertheless, most of the existing models regard only static snapshots and are not able to picture the dynamic load fluctuations during the entire milling process. This paper describes a data-driven way for a more detailed prediction of the power consumption for a milling process using Machine Learning techniques. To increase the accuracy we used separate models and machine learning algorithms for different operations of the milling machine to predict the required time and energy. The merger of the individual models allows finally the accurate forecast of the load profile of the milling process for a specific machine tool. The following method introduces the whole pipeline from the data acquisition, over the preprocessing and the model building to the validation.<br
Keywords: energy prediction; time prediction; power load prediction; milling process; machine learning; regression

Enhancing Energy Efficiency in Machining through Digital Twin Technology: Predictive Modeling of Thermal Loads in Machine Tool Spindles - Bani-Hani, Mohammad; Hanenkamp, Nico (Procedia CIRP, 2025)
Improving energy efficiency in machining processes is a critical objective in state-of-The-Art-manufacturing. The spindle system of machine tools, a primary source of thermal loads, plays a significant role in determining energy efficiency. Excessive heat generation not only affects spindle performance but also increases energy demand, particularly for cooling systems. This study introduces a digital twin-based predictive framework designed to optimize cooling loads in machine tool spindles by integrating advanced mechanical and thermal modeling techniques. The framework leverages predictive models to accurately estimate mechanical load profiles, which are derived from machining parameters such as tool paths, cutting forces and feed rates. These mechanical profiles are coupled with thermal models to simulate heat generation and dissipation dynamics within the spindle system. By integrating these sub-models, the framework enables precise prediction of cooling requirements, ensuring that the spindle operates within optimal temperature ranges without unnecessary energy consumption.
CRIS-Team Scopus Importer:2025-05-02
Keywords: Digital Twin; Machine Tools; Machining Optimization; Material Removal Simulation; Thermal Modeling

Erweitertes Prozessverständnis erleichtert das Bauteilfinishing - Amon, Sven; Pour Abdollahyan, Fardin; Gross, Daniel; Hanenkamp, Nico (Werkstatt und Betrieb, 2019)
Das Finishing steht durch vorwiegend manuelle Bearbeitungskonzepte im Widerspruch der Automatisierungstrends. Neue Erkenntnisse zum Finishen mit Trockeneis ermöglichen Anwendern Ansätze für leicht zu automatisierende Technologien bereits im Vorfel
Keywords: Entgraten; Abtragen von Stützstrukturen; Reinigung; Finishing; Automatisierung

Experimental investigation of ultrasonic vibration-assisted cryogenic minimum quantity lubrication for milling of Ti-6Al-4V and grinding of Zerodur - Blasl, Jacqueline; Lichtinger, Klaus; Vieltorf, Fabian; Zaeh, Michael F.; Hanenkamp, Nico (Production Engineering, 2023)
Increasing demands on component properties are leading to the development of high-performance materials for which conventional production methods are reaching their limits from an economic and ecological point of view. In recent years, two technologies have been developed that show great potential compared to conventional machining processes, particularly in machining high-performance materials such as the titanium alloy Ti-6Al-4V. Ultrasonic-assisted machining leads to reduced cutting forces and increased tool life. Cryogenic minimum quantity lubrication prevents the occurrence of high machining temperatures and allows higher material removal rates without a negative impact on tool life. This paper shows the influence of ultrasonic-assisted milling and grinding processes in combination with cryogenic minimum quantity lubrication on the machinability of the high-strength materials Ti-6Al-4V and Zerodur. The investigation addressed cutting forces, tool wear, and surface roughness. The superposition of the technologies resulted in longer tool life and lower tool wear for both milling and grinding. However, the surface roughness was consistently higher due to the ultrasonic superposition. Nevertheless, machining with ultrasonic vibration-assisted cryogenic minimum quantity lubrication has great potential for difficult-to-machine materials, especially due to the reduction in tool wear.
CRIS-Team Scopus Importer:2023-07-28
Keywords: Cryogenic cooling; Minimum quantity lubrication; Ti-6Al-4V; Ultrasonic vibration; Vibration-assisted machining; Zerodur

Gratentfernung durch Trockeneis - Amon, Sven; Viner, Alexander; Hanenkamp, Nico (JOT, Journal fuer Oberflaechentechnik, 2022)
Die Entgratung stellt insbesondere bei schwer zugänglichen Graten eine Herausforderung dar. Trockeneisstrahlen kann durch die Verwendung von recyceltem CO2 einen sauberen, nachhaltigen und wirtschaftlichen Lösungsansatz bieten. Erste Ergebnisse einer laufenden Studie zeigen eine zuverlässige Gratentfernung bei verschiedenen metallischen Werkstoffen.<br
Keywords: Entgratung; Trockeneisstrahlen; Finishing; Endbearbeitung

Grundstein für neuartige Bearbeitungsstrategie gelegt - Blasl, Jacqueline; Vieltorf, Fabian; Hanenkamp, Nico; Zaeh, Michael (VDI-Z Integrierte Produktion, 2021)
Bei neuartigen Werkstoffen stoßen herkömmliche Fertigungsverfahren aus ökonomischer und ökologischer Sicht an ihre Grenzen. In Forschungsprojekten werden derzeit die Ultraschallbearbeitung und die kryogene Minimalmengenschmierung (kMMS) betrachtet, die sich bei schwer zerspanbaren Werkstoffen gegenüber konventionellen spanabhebenden Verfahren auszeichnen. Im Verbundprojekt „KryoSonic“ wird die Überlagerung beider Technologien bei Fräs- und Schleifprozessen untersucht.<br

Hybrid Supply System for Conventional and CO2/MQL-based Cryogenic Cooling - Hanenkamp, Nico; Gross, Daniel; Amon, Sven (Procedia CIRP, 2018)
Increasing demand for difficult-to-cut materials challenge conventional cooling techniques to their limit. The durability of the tool is often reduced and cutting parameters such as feed rate or depth of cut have to be adjusted with a negative impact on productivity. Therefore, innovative cooling technologies have to be developed and integrated into new and existing machining equipment. The article describes the development of a hybrid cooling concept offering the flexibility to assign conventional or cryogenic cooling to incremental process steps. The developed cryogenic cooling supply system controls the flow of liquid carbon dioxide regarding density, flow rate and temperature before the lubrication media is injected by a high precision pump into the same tube. This approach significantly reduces the integration effort especially for internal cooling before being applied to a drilling process with a rotating tool of 50CrMo4. The challenges for the integration in the machine tool consist in the interface between spindle and tool holder and the tool itself due to the potential expansion of CO2 leading to undesired cooling before reaching the tool center point. Therefore, each interface has been investigated and requirements for cryogenic-compatible tools have been defined. Finally, different lubrication fluids combined with CO2-based cryogenic cooling have been investigated regarding tool durability for a milling process of Ti6Al4V. The results show that different oils have significant impact on the process performance offering a perspective for further research.<br
Keywords: Cryogenic Cooling; Minimum Quantity Lubrication

Implementation and potentials of a machine vision system in a series production using deep learning and low-cost hardware - Würschinger, Hubert; Mühlbauer, Matthias; Winter, Michael; Engelbrecht, Michael; Hanenkamp, Nico (Procedia CIRP, 2020)
For manufacturing processes there is a need to ensure an efficient production and to fulfill the increasing quality requirements. To handle these challenges, Machine Vision Systems can be used for process monitoring and quality control. In this paper the implementation and thereby the potentials of such a system in a series production using Transfer Learning with low cost hardware is introduced. The necessary steps, from the hardware implementation, the data acquisition, the preprocessing over the optimization and the application are depicted. Finally we show that the proposed solution can fulfill defined requirements and can compete with a professional Machine Vision System.<br
Keywords: Machine Vision; Manufacturing; Series Production; Image ClassificationTransfer Learning; Low Cost; Data Acquisition

Influence of Additivation of Bio-Based Lubricants on Sprayability and Solubility for Cryogenic Minimum Quantity Lubrication - Meier, Trixi; Lermer, Michael; Gross, Daniel; Hanenkamp, Nico (Manufacturing Driving Circular Economy. GCSM 2022, 2023)
The development of innovative cooling lubrication strategies is significantly driven by the need to machine materials resistant to high temperatures while taking into account both ecological and economic aspects. Cryogenic minimum quantity lubrication (CMQL) represents a compromise satisfying both efficiency and sustainability in the manufacturing process. A minimal amount of oil is added to the cryogenic medium carbon dioxide (CO2) to ensure both cooling and lubrication during tool engagement. In this context, vegetable oils, so-called triglycerides, can be used with respect to the cooling lubrication concept. The aim of this paper is to analyze various bio-based oils with regard to their solubility, spraying and flow behavior and to investigate the influence of additives on the performance. During the lubrication tests, the additives have shown no influence on the lubricating effects. Thus the chemical properties of the base oils primarily influence the properties with regard to solubility and spray behavior. Finally, the collected results were correlated with machining tests showing only a limited correlation with the aforementioned lubrication tests.
Keywords: CMQL; Milling; Liquid carbon dioxide; Bio-based lubricants

Influence of Carbon Dioxide Temperature on Sprayability and Solubility in Cryogenic Minimum Quantity Lubrication with Bio-Based Lubricants - Meier, Trixi; Lermer, Michael; Gross, Daniel; Hanenkamp, Nico (Manufacturing Driving Circular Economy. GCSM 2022, 2023)
Cryogenic minimum quantity lubrication (CMQL) represents a compromise satisfying both efficiency and sustainability in many manufacturing processes. In previous series of experiments a variation of the thermodynamic state of the cryogenic medium taken from riser bottles could be observed. Consequently, the aim of this study was to specifically control the thermodynamic state of the CO2 and, associated with this, the density after removal from the riser bottles. To achieve this objective conventional cooling was implemented for the CO2 after withdrawal from the riser bundle in order to have a constant liquid state of the CO2 during feeding. The density of the cryogenic medium could be raised from ρ = 550 kg/m3 to over 800 kg/m at a mass flow rate of m˙ CO2 = 5 kg/h with the applied cooling method and can also be stabilized regarding the density pulsation. Subsequently, the effects of temperature-controlled CO2 on the sprayability and solubility in CMQL were examined and resulted in increased atomization of the oils and widening of the spray corridor with a greater main spray length and intensity. In addition stable conditions for the CMQL-supply to the manufacturing process were achieved by a lower pulsation of the CO2-oil mixture.
Keywords: CMQL; Liquid carbon dioxide; Bio-based lubricants

Influence of dry ice blasting process properties on surface roughness and residual stresses of machined and additive manufactured workpieces - Amon, Sven; Jobst, Andreas; Merklein, Marion; Hanenkamp, Nico (Procedia CIRP, 2022)
Dry ice blasting has shown the potential to remove metallic burrs after machining processes and support structures after additive manufacturing. During blasting, process parameters need to be chosen depending on the material and the geometric properties of the burr. However, dry ice blasting affects the local material properties on a micro level and improper blasting parameters may lead to changes in the part surface. In this article, correlations and interactions between dry ice blasting parameters and resulting specimen roughness and residual stresses are identified for machined and additive manufactured metallic materials.<br
Keywords: dry ice blasting; metallic edge zone; deburring; post-processing; residual stresses

Initial Study on Milling in an Ultrasonically Excited Metalworking Fluid Bath - Gross, Daniel; Eichinger, Miriam; Selzam, Jan Harald; Hanenkamp, Nico (Lecture Notes in Mechanical Engineering, 2025)
Energy and resource efficiency are seen as key drivers of the industrial transformation towards a low carbon economy. In particular, machine tools, which are essential to value creation, have a significant share of industrial greenhouse gas emissions due to their high-energy consumption. The energy demand for the provision and supply of metalworking fluids (MWF) alone can account for up to 25% of the total energy demand. The aim of this study is to investigate and fundamentally design an alternative cooling lubricant concept. This concept does not require continuous pumping of the coolant supply. Instead, the milling operation takes place in an immersion bath filled with metalworking fluid. An additional ultrasonic (US) actuator causes the coolant to vibrate, allowing the coolant to penetrate deeper into the cutting zone. The machining tests include a comparison of classic flood cooling, immersion bath milling and immersion bath milling with US stimulation. To compare the processes, the flank wear, the workpiece surface roughness and the bending moments due to the cutting forces were analyzed. The energy assessment allows a final evaluation of the processes.
CRIS-Team Scopus Importer:2025-02-28
Keywords: energy efficiency; immersion bath; Milling; ultrasonic

Innovative Refrigeration Technology for Machine Tools with Sustainable Refrigerants and Digital Twins - Bani-Hani, Mohammad; Stemmler, Timon; Hanenkamp, Nico (Procedia CIRP, 2024)
This article investigates the trend of assessing energy efficiency, sustainability and greenhouse gas emissions in the operation of 5- axis milling machine tools. This research aims to predict the cooling load by thermal models control within the main spindle system to ensure that cooling devices are dimensioned adequately and to keep it running under optimal conditions leading to improve the overall efficiency. In order to achieve this goal, a digital twin approach is currently being developed utilizing commercial software which consists of four primary models. A simulation model for material removal is used to predict the mechanical load required for the milling process to finish the CAD model. The second model is the spindle control model to determine the electric currents needed to operate the induction motor at the specified mechanical power. This model provides the electric current data to the lumped-parameter thermal networks (LPTN) model, which is proposed to accurately represent the heat dissipation from the motor and spindle systems towards the cooling channel in the main spindle system. Subsequently, the task at hand involves making an estimate of the necessary outlet temperature derived from the refrigeration unit model, which is essential for effectively covering the thermal energy produced by the spindle system.<br
Keywords: Digital Twin; Lumped-parameter Thermal Networks; Milling; Machine Cooling

Investigation of Carbon Dioxide Based Blasting Technologies as Cryogenic Deburring Method for Titanium Alloy and Stainless Steel - Gross, Daniel; Heinz, Andrea; Amon, Sven; Meier, Trixi; Schmand, Ralf; Hanenkamp, Nico (Applied Mechanics and Materials, 2018)
This paper aims to expand the use of CO2 blasting by investigating a cryogenic deburring method for machined metallic materials. In advance to the actual deburring experiments, a streaming analysis based on high-speed video records was conducted for different blasting technologies, in order to gain deeper knowledge about their underlying active principles. For the titanium alloy Ti-6Al-4V and the stainless steel X6CrNiMoTi17-12-2, deburring experiments with three different blasting techniques were conducted and evaluated. It has been shown that cryogenic deburring has the potential to represent an alternative deburring solution for metals.
Keywords: cryogenic deburring; deburring with CO2; CO2-based blasting technologies; CO2 snow blasting; dry ice blasting

Investigation of lubricating oils from renewable resources for cryogenic minimum quantity lubrication - Meier, Trixi; Gross, Daniel; Hanenkamp, Nico (MM Science Journal, 2021)
Cryogenic minimum quantity lubrication using liquid carbon dioxide (CO2) has increasingly become the focus of research in recent years. With this cooling strategy it is possible to cool and lubricate the cutting zone individually by regulating the oil and liquid CO2 flow. The oil used has a significant influence on the process stability and performance. The aim of this study is to identify the influence of 15 different base oils from renewable sources on a milling process of X2CrNiMo17-12-2 with cryogenic minimum quantity lubrication. For this purpose, a non additivated sunflower, coconut and rapeseed oil and additional bio-based oils, such as synthetic ester and fatty alcohol, will be tested and compared to a conventional mineral oil regarding wear, process forces and productivity. In addition, the impact of the bio-based oils on rough turning of X2CrNiMo17-12-2 and finishing turning of 100Cr6 with cryogenic minimum quantity lubrication is evaluated and compared to the milling performance. The results have been analyzed in comparison to conventional emulsion flood cooling and recommendations have been given for the future development of sustainable lubricants to be applied with cryogenic cooling strateg
Keywords: CMQL; milling; turning; bio-based oils; carbon dioxide

Investigation of the effects of CO2 pre-cooling on the cooling capacity for cryogenic cooling in machining operations - Meier, Trixi; Selzam, Jan Harald; Röckelein, Andreas; Hanenkamp, Nico (CIRP Journal of Manufacturing Science and Technology, 2024)
Abstract: Liquid carbon dioxide (LCO2) based cryogenic cooling has shown promising results in terms of wear reduction, productivity increase and energy efficiency when machining high-temperature materials. For process-safe use with low pulsation, CO2 must be fed in the liquid state to cool the process zone. LCO2 is typically stored in riser bottles in which gaseous and liquid aggregate state coexist. A preliminary study has already shown that the liquefied state of the CO2 can be stabilized by pre-cooling. In this paper, the influence of a heat exchanger as a pre-cooling system on the cooling capacity of the CO2 is investigated and the required energy consumption is compared to unstabilized CO2, pressure increased CO2 and compressed air. It has been shown that pre-cooling leads to a more energy-efficient increase in the cooling capacity of the CO2 compared to pressure increased CO2. <br
Keywords: Cryogenic minimum quantity lubrication; Liquid carbon dioxide; Density enhancement; Cooling capacity; Machining; Energy effiency

Investigation of the influence of lubricating oils on the turning of metallic materials with cryogenic minimum quantity lubrication - Gross, Daniel; Bigelmaier, Matthias; Meier, Trixi; Amon, Sven; Ostrowicki, Nicolai; Hanenkamp, Nico (Procedia CIRP, 2019)
Nowadays, cooling and lubrication for cutting processes in industry are mostly based on flood cooling. The enormous quantities of lubricants are not only harmful for the environment and employees, but also require additional infrastructure and pre-treatment, while processed parts require an additional cleaning step due to metallic swarf which leads to high manufacturing costs. The cryogenic minimum quantity lubrication could serve as an alternative cooling and lubrication concept, which might be suitable for high-alloyed steels and titanium alloys as well. Within this work the potential of this new concept of cooling and lubrication was investigated by the utilization of different lubricants for turning of Ti6Al4V, X5CrNi18-10 and 42CrMo4 workpieces with a main focus on cutting forces, tool wear and resulting surface roughness. Required data indicates that the cryogenic minimum quantity lubrication might indeed be suitable to replace the conventional wet processing routes. The proper lubricants are selected to match the material to be machined.<br
Keywords: Turning; Cryogenic Machining; Minimum Quantity Lubrication; Ti6Al4V; 42CrMo4; X5CrNi18-10

Investigation of the influence of the additivation of a biological metalworking oil in cryogenic machining - Meier, Trixi; Seydaack, Milena; Gross, Daniel; Hanenkamp, Nico (Procedia CIRP, 2022)

Investigation on the productivity of milling Ti6Al4V with cryogenic minimum quantity lubrication - Gross, Daniel; Appis, Maximilian; Hanenkamp, Nico (MM Science Journal, 2019)
Because of its unique material properties, Ti6Al4V is used for components in the aerospace industry which are subject to high mechanical and thermal loads. Due to that, this material is considered as difficult to cut from a machining point of view. In order to improve productivity in machining Ti6Al4V the use of an effective cooling and lubrication strategy is necessary. This challenge can be managed with the innovative hybrid technology (CMQL) combining liquid carbon dioxide (CO2) and minimum quantity lubrication (MQL) being under investigation in this article. At first, investigations on the liquid CO2 release behavior and the application of oil by the CMQL were conducted. Secondly, CNC milling experiments were carried out using carbide end mills. The CMQL technique was compared to MQL and flood cooling in respect to tool wear, cutting moment and surface integrity. For the milling operations the cooling parameters of the CMQL as well as the cutting parameters were modified, in order to reduce tool wear or increase productivity. The analysis revealed that the development of an appropriate CO2 free jet and a continuous application of oil by the CMQL is achievable without changing the state of aggregation of CO2 from liquid to supercritical. The analysis of the milling experiments indicated that CMQL is more advantageous compared to flood cooling and MQL for higher cutting parameters.<br
Keywords: Carbon dioxide; cryogenic; CMQL; Ti6Al4V; milling; spray test

Maschinelle Lernverfahren für die Praxis - Praxisnahes Qualifizierungskonzept für Industriesegmente wie Automotive und Maschinenbau - Mühlbauer, Matthias; Würschinger, Hubert; Hanenkamp, Nico (VDI-Z Integrierte Produktion, 2019)

Maschinelle Lernverfahren zur Digitalisierung manueller Ablese- und Messvorgänge - Mühlbauer, Matthias; Würschinger, Hubert; Hanenkamp, Nico; Funtikov, Svyatoslav (Industrie 4.0 Management : Gegenwart und Zukunft industrieller Geschäftsprozesse, 2023)
Im Fabrikbetrieb kommen häufig Messmittel zum Einsatz, bei denen noch keine automatische Abspeicherung oder Weiterverarbeitung des gemessenen Werts erfolgt. Mitarbeiter müssen in diesem Fall den Messwert manuell er-fassen und weiterverarbeiten. Folgend wird ein Ansatz zur optischen Erfassung und Digitalisierung von Messwerten mithilfe Maschineller Lernverfahren vorgestellt. Dies soll zur Entlastung der Mitarbeiter beitragen, Ablesefehler reduzieren sowie eine automatisierte Dokumentation ermöglichen.<br
Keywords: Digitalisierung; Bildverarbeitung; Maschinelles Lernen; Objekterkennung

Milling of Ti6Al4V with carbon dioxide as carrier medium for minimum quantity lubrication with different oils - Gross, Daniel; Blauhöfer, Markus; Hanenkamp, Nico (Procedia Manufacturing, 2020)
Machining of difficult-to-cut materials such as nickel-based or titanium alloys lead to high static, dynamic and thermal tool loads. A crucial role is given to the used cooling lubricant. Here, the cryogenic cooling with liquid nitrogen or carbon dioxide has been investigated in recent years as a possible alternative to conventional flood cooling. The following article deals with the further development of CO2-based cryogenic cooling combined with a minimum quantity lubrication (MQL) injected directly into the liquid CO2 phase. The focus of the investigation is the experimental selection of MQL oils for this application. For this purpose, the potential of various base oils and additivated lubricants for the CO2 assisted milling of Ti6Al4V has been investigated. The suitability assessment of the lubricants has been based on the optical measurement of wear progress along the cutting edge, recording the effective cutting forces and surface roughness. Furthermore, a mathematical compensation method is presented for the compensation of the measured value drift caused by low temperatures. The results show that the potential of cryogenic MQL is largely determined by the base oil being used. It has also been demonstrated that the use of bio-based ester oils for the present process is an alternative to mineral oil-based lubricants.<br
Keywords: CMQL; milling; Titanium; force measurment

Milling Strategy Design to Improve Vibration Behavior, Tool Wear and Surface Roughness in Machining - Ju, Shu; Hanenkamp, Nico (Proceedings of WCSE 2022 Spring, 2022)
Uncontrollable vibration behavior during the milling process impairs the surface quality of the workpiece and escalate the machine damage as well as machine and tool wear. In this work, the impact of various milling strategies with control optimization for three different types of milling operations are studied. To objectively quantify the process quality, the machining time, the width of tool wear marks and the surface quality after each experiment as well as the vibration amplitude and the bending moment of the tool holder during the process have been measured and evaluated. For every milling type, three milling strategies with three iterative experiments each have been carried out. As a result, a database with vibration-related data and information for different milling strategies has been established. Thus, the machining process of workpieces with diverse geometric elements and the corresponding manipulated variables can be assessed regarding the vibration and tool wear behavior. Based on the experimental results, the potentials of the vibration-minimized milling strategies and tool path design in enhancing the process stability, the productivity and the tool life can be verified.<br
Keywords: Milling operations; chatter suppression; process optimization

Model-Based Correlation Analysis of Machine Control Parameters and Process Vibration Amplitudes by the Example of Milling - Ju, Shu; Reitenspieß, Max; Zhang, Kai; Hanenkamp, Nico (Manufacturing Driving Circular Economy. GCMS 2022, 2023)
In machining processes, system-immanent process vibrations lead not only to lower surface quality of workpieces but also to the degradation of the machine and tool wear. Effectively minimizing process vibration amplitudes without costly software or hardware add-ons is a research topic that demands further investigation. In this regard, this article focuses on the further development of a holistic milling process model as well as the experimental and simulation-based vibration analysis. The interaction between the nonlinear behaviors of the cascade controlled electric motors and the process parameters are practically evaluated. Moreover, based on the experimental and simulation results, a correlation analysis of the machine control parameters and the process vibration amplitude has been implemente
Keywords: integrated simulation system machining process vibration cascade control

Nachhaltige Prozessfähigkeit der Wiederbeschaffungszeit bei autonomen Transportsystemen - Hanenkamp, Nico; Ochs, Christian; Müller, Martin (Industrie-Management : Zeitschrift für industrielle Geschäftsprozesse, 2018)

Optimierte Programmplanung durch Ressourcenmanagement - Hanenkamp, Nico (Productivity Management, 2013)
Keywords: Resource management; Program planning; Supply chain management

Realisierung eines digitalen Energieausweises für industrielle Erzeugnisse - Hanenkamp, Nico; Henkel, Roberto; Gessner, Philipp (Zeitschrift für wirtschaftlichen Fabrikbetrieb, 2017)

Ressourceneffizienz durch Schnittstellenoptimierung - Hanenkamp, Nico; Ju, Shu (Technik in Bayern, 2019)

Ressourceneffizienz durch Schnittstellenoptimierung zwischen Produktionsprozess und Maschine - Hanenkamp, Nico (Technik in Bayern, 2019)

Standard business process for efficiency improvement in production cells - Hanenkamp, Nico (Applied Mechanics and Materials, 2013)
Keywords: Lean management; Toyota production system; Performance management

Superposition of cryogenic and ultrasonic assisted machining of Zerodur - Vogt, C.; Thiess, H.; Blasl, Jacqueline; Hanenkamp, Nico; Lichtinger, K. (Proceedings of SPIE - The International Society for Optical Engineering, 2023)
Cryogenic machining is a cooling strategy that has recently been frequently found in research in machining processes for materials such as inconel or titanium. In particular it is reported that these processes are more efficient in terms of tool life and material removal rate compared to those with water-based cooling lubrication. An increase in efficiency and productivity has significant potential from a cost perspective, especially when grinding Ceramic Matrix Composite materials and similar. These processes are used, for example, in the lightweighting of telescope mirrors made of e.g. fiber-reinforced silicon carbide, or Zerodur. An increase in productivity would be clearly noticeable in the manufacturing costs due to normally long machining times. In the "KryoSonic" project, we investigated whether and to what extent the use of cryogenic machining affects the rough machining of Zerodur with and without ultrasonic support.
CRIS-Team Scopus Importer:2023-11-17
Keywords: brittle chipping; cryogenic machining; Grinding; ultrasonic

SUPPORTING MANUAL CONTOUR AND SURFACE PROCESSING WITH THE HELP OF AUGMENTED REALITY - Mühlbauer, Matthias; Auer, Alexander; Würschinger, Hubert; Hanenkamp, Nico (MM Science Journal, 2023)
When manually processing complex contours or surfaces, there is a risk of incomplete or unnecessary multiple processing. The support of such processes with an augmented reality (AR) application will be presented in this work using the example of manual deburring. Firstly, the positions of the component and tool are determined based on camera recordings. For this purpose, approaches for 6 Degrees of Freedom (DoF) pose estimation will be utilized. Secondly, the correct and complete processing is concluded by further analyzing the extracted data. For example, the distance of the objects to each other. In the third step, the processing result is visualized to aid the worker. Finally, the system is validated through a study. The results show that with the help of image targets a robust recognition of the objects at a normal execution speed and thus process support can be realized.
CRIS-Team Scopus Importer:2023-12-22
Keywords: assistance system; Augmented reality; contour and surface processing; deburring; manual processes; object detection

Sustainable Dry Turning of Aluminum Alloys Using Pulsed High-Pressure Cryogenic Jet Cooling - Selzam, Jan Harald; Enslein, Niklas; Gross, Daniel; Hanenkamp, Nico (Lecture Notes in Mechanical Engineering, 2025)
As well as producing contamination-free parts, dry machining is a sustainable alternative to conventional machining processes using metalworking fluids. Despite these benefits, chip breaking and chip removal are challenges in dry machining processes, particularly when turning ductile materials, which are known for continuous chip formation and therefore long chips. Due to their tendency to become entangled around machine components, these chips have to be removed manually, posing a risk to productivity and operator health. Recent studies have demonstrated the effectiveness of pulsed high-pressure emulsion cooling for chip breaking. This paper aims to transfer these findings to sustainable dry machining and investigates the influence of pulsed high-pressure cryogenic jet cooling on chip breaking and chip removal. Therefore, liquid CO2 at pressures up to 200 bar is used as a cooling medium in turning processes of two aluminum alloys and is applied continuously or pulsed to the machining area. It has been shown that high-pressure cryogenic jet cooling improves chip breaking and chip removal, allowing a wider range of cutting parameters, widening the process window and providing a higher level of sustainability, productivity and safety in dry machining.
CRIS-Team Scopus Importer:2025-02-28
Keywords: Aluminum; Carbon dioxide; Dry turning; Pulsed high-pressure cryogenic jet cooling; Sustainable machining

Technologieentwicklung kryogener Entgratungsstrategien für metallische Werkstoffe - Amon, Sven; Hanenkamp, Nico (2022)
Keywords: Kryogene Entgratung; Kryogene Entstützung; Trockeneisstrahlen

Theoretical Investigation of the Influence of Different Chamber Geometries on the Agglomeration Capacity of Carbon Dioxide - Gross, Daniel; Ferguson, Nikolas; Amon, Sven; Hanenkamp, Nico (Applied Mechanics and Materials, 2017)
This paper addresses the complicated process of carbon dioxide particle formation (agglomeration), which is essential for carbon dioxide snow blasting. Most effective process methods in this field possess a dedicated location where agglomeration is likely to occur. Research has shown that successful agglomeration is a key factor when cleaning or deburring with solid carbon dioxide. The following describes the mechanisms of carbon dioxide (CO2) snow agglomeration inside this so-called agglomeration chamber. The elements of larger size, as well as an irregular shape directly lead to the increase of effectiveness. Therefore, it is necessary to determine how to improve this process for the purpose of dealing with difficult workpieces and materials and broaden the possibilities of carbon dioxide blasting. One of the main factors of agglomeration is turbulence. In short, the more turbulent activity that takes place, the better is the particle formation of solid carbon dioxide. Numerous geometries were created with different inserts, such as static mixers or angled tubes, in hope to increase turbulence. The basic idea is to implement these geometries in computational fluid dynamics (CFD) and finally proceed to an evaluation and comparison of the simulation results, in order to select the best candidates for optimization and realization.
Keywords: Agglomeration; Carbon Dioxide; Computational Fluid Dynamics (CFD)

Transfer Learning für visuelle Kontrollaufgaben - Würschinger, Hubert; Mühlbauer, Matthias; Hanenkamp, Nico (wt Werkstattstechnik - Online, 2020)
In der industriellen Praxis wird eine Vielzahl von Prozessund Qualitätskontrollaufgaben visuell von Mitarbeitern oder mithilfe von Kamerasystemen durchgeführt. Durch den Einsatz Künstlicher Intelligenz (KI) lässt sich die Programmierung und damit die Implementierung von Kamerasystemen effizienter gestalten. Im Bereich der Bildanalyse können dabei vortrainierte Künstliche Neuronale Netze verwendet werden. Das Anwenden dieser Netze auf neue Aufgaben wird dabei Transfer Learning genannt. <br
Keywords: Künstliche Intelligenz; Produktion; Qualitätssicherung

Vorhersage der Prozessstabilität mit Maschinellem Lernen - Potenziale Künstlicher Intelligenz zur frühzeitigen Erkennung von Abweichungen bei der pharmazeutischen Abfüllung - Mühlbauer, Matthias; Würschinger, Hubert; Hanenkamp, Nico; Schmehling, Moritz; Krause, Björn (Industrie 4.0 Management : Gegenwart und Zukunft industrieller Geschäftsprozesse, 2020)